Tacit and Explicit Knowledge in the Costa Rican Food Industry: Implications for Innovation Education - Soto Kiewit, Luis Diego (2024)
This article offers a reflection on the impact of explicit and tacit knowledge on the development of innovations in seven Costa Rican food industry companies that are members of the Costa Rican Chamber of Food Industry (CACIA, in Spanish). This was done with the purpose of deriving implications for the Costa Rican educational system. The research was a qualitative approach, based on the application of semi-structured interviews with officers in each of the companies. The results show that both forms of knowledge play a central role in the achievement of various innovations in each of the organizations. The results also suggest six implications for the education system as a socializing institution and a builder of knowledge and skills for a society that demands innovative people.